Layered double hydroxides for aluminium alloys corrosion resistance - Rangel, C. M. (2010)
Layered Double Hydroxides (LDHμs), represented by the general formula [MII (1-x)MIIIx(OH)2[An-x/n].zH2O or [MIMIII2(OH)6[An-1/n].zH2O], where MI, MII, MIII are mono-, di- and tri-valent metal cations, are being researched as anion-exchange materials with interesting intercalation chemistry that accommodate a wide range of applications including corrosion resistance. In this work, layered double hydroxides containing a monovalent (Li+) and trivalent (Al3+) matrix cations, have been synthesized and characterised using X-ray diffraction, FTIR and SEM. LDHμs were prepared by a simple co-precipitation method using metal hydroxides and metal salts in an alkaline solution. Formation of LDHμs on the metal surface of Al alloys were attempted with excellent results. Pitting corrosion was inhibited on Aluminium 2024-T3 with an extensive capability to withstand the presence of high concentrations of chloride ions. The formation of DHLμs is thought to be responsible for inhibition which is demonstrated to be under diffusion control. The action of DLHμs on copper is demonstrated in separated experiments using pure copper samples in similar experimental conditions as for the alloy, in an extensive